Notes on the genus Conchapelopia Fittkau (Diptera: Chironomidae: Tanypodinae) from southern China, with description of a new species - Niitsuma, Hiromi; Tang, Hongqu (Zootaxa, 2017)
Two interesting species, Conchapelopia togamaculosa Sasa & Okazawa and a new species, Conchapelopia brachiata sp. n., were collected from southern China. The male, pupa and larva of the new species are described, and new distributions of the former species are noted. Although the male of the new species is very distinct from that of the former in the hypopygial median volsella, the pupa and larva stunningly resemble those of the former.